The Influence Of The Ethnomathematicss-Based Multy Representation Discourse Learning Model On Mathematical Communication Skills And Self-Confidence Of Junior High School Students - Jaka Wijaya Kusuma; Zaenuri Zaenuri; Rochmad Rochmad; Emi Pujiastuti; Hamidah Hamidah (Universitas Negeri Semarang, 2022)
Abstrak. Ethnomathematicss-based multy representation discourse is a learning model that emphasizes the use of multi-representation in a classroom setting using cultural relationships in the context of life that can improve students' mathematical communication skills and self-confidence. The purpose of the study was to find out how the influence of the Ethnomathematics based diskursus multy Representation model on students' mathematical communication skills and self-confidence. This study used a type of pretest-posttest control group design experiment. This research was carried out in the even semester of 2022 with samples of class VII B as the experimental class and VII A as the control class. Data collection techniques use tests and questionnaires. Data analysis techniques use t-test analysis, Effect Size, and questionnaire percentage. Based on the results of the study, it is known that the influence of the Ethnomathematics based diskursus multy Representation learning model on students' mathematical communication skills is very high and student self-confidence after being given the Ethnomathematics based diskursus multy Representation learning model is relatively high.